Estimation of Equilibrium Exchange Rates in the WAEMU : A Robustness Analysis - Saxegaard, Magnus (IMF Working Papers; Working Paper ;, 2007)
Using the FEER approach we investigate the long-run equilibrium paths of the real effective exchange rates (REERs) of countries in the West African Economic and Monetary Union (WAEMU). In an attempt to address econometric estimation uncertainty, we employ both single-country (Johansen and ARDL) and panel-data (FMOLS and PMG) cointegration techniques. We find that (i) much of the long-run behavior of REERs in WAEMU countries can be explained by fluctuations in terms of trade, government consumption, investment, and productivity; (ii) the use of different econometric techniques suggests that there is significant uncertainty about the path of the underlying equilibrium REERs and the degree of exchange rate misalignment, which underscores the need for robustness analyses in exchange rate modeling; and (iii) results from panel-data cointegration may sometimes be useful, but should always be complemented with single-country estimations to ensure that the results take into account country-specific characteristics.